Good Corporate Governance and Corporate Social Responsibility Disclosure: Before and During The Covid-19 Pandemic (E-Jurnal Akuntansi, 2026)
This research aims to determine the effect of Good Corporate Governance (GCG) through the board of commissioners, the board of independent commissioners, managerial ownership, and institutional ownership on Corporate Social Responsibility Disclosure (CSRD) before and during the Covid-19 pandemic. CSRD is measured based on GRI Standards. The sample used is Energy sector companies listed on Indonesia Stock Exchange (IDX) in 2018-2021 with 104 observations. Data were analyzed using panel data regression with Eviews software. The research results show that the board of commissioners has a positive effect on CSRD before and during the Covid-19 pandemic which supports agency theory and the economics of information, while the board of independent commissioners, managerial ownership, and institutional ownership have no effect on CSRD before and during the Covid-19 pandemic. Practically, companies need to increase CSRD intensity, especially on economic, environmental and social topics.
Keywords: Corporate Social Responsibility; Disclosure; Good Corporate Governance; GRI Standards.